PENGARUH PENERAPAN MULTIMEDIA PEMBELAJARAN INTERAKTIF (MPI) BERBASIS CANVA TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN KREATIVITAS MURID SDN 1 TAMANSARI : - - Junika, Juni Kartika; Darmiyani, Darmiyani; Ida Ermiana, Ida Ermiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital education in the 4.0 era demands innovative learning media that can provide a more interactive, adaptive, and relevant learning experience for elementary school students. Canva-based multimedia is an effective alternative because it provides an attractive, flexible visual design that is easy for both teachers and students to operate. The integration of image, animation, audio, and text elements in one platform allows students to process information through various representational channels, thereby increasing engagement, focus, and deeper understanding of concepts. The use of Canva in learning has also been proven to contribute to the development of critical thinking skills and creativity, as it encourages students to analyze information, evaluate ideas, and produce original visual works. In addition, this media can create a more collaborative learning atmosphere, provide space for exploration, and increase learning motivation through an attractive display that is in line with the characteristics of the digital generation. Overall, the implementation of Canva-based interactive multimedia has great potential in improving the quality of the learning process and outcomes of elementary school students, especially in higher-level cognitive aspects that require active stimulation and meaningful learning experiences.